Post-democratic regimes and the businessification of the state and civil society - Hewison, Kevin (Quezon City University of the Philippines Center for Integrative and Development Studies, 2018)
The post-democracy literature emphasizes a diminution of democracy as the state becomes attuned to the interests of business and itself operates as a business. In this paper, that process is called ?businessification.? It is suggested that business and a businessified state are now engaged in a two-pronged effort to businessify the organizations of civil society. This is the struggle for civil society, for the various processes that come together as businessification means that civil society organizations (CSOs) will tend to be supportive of?or at least non-challenging to?the state and business. For Petras (1999, 435), there has been a tendency for ?apolitical? postures amongst NGOs, observing that ?their focus on self-help depoliticizes and demobilizes the poor.? Yet applying the insights of the post-democracy literature, it is seen that as bussinessification takes hold of CSOs, there is a diminution of activism that contributes to the narrowing of political space, the rise of anti-politics, and the domination of business elites. Recognizing that mechanisms associated with businessification weaken civil society activism acknowledges that there is an ongoing struggle for the control of civil society.
Keywords: Privatization -- Philippines; Government business enterprises -- Philippines; Business enterprises -- Philippines -- Government policy; Civil society -- Philippines -- Business enterprises; Philippines -- Economic conditions -- 1986-.